Protective Effects of Smilax glabra Roxb. Against Lead-Induced Renal Oxidative Stress, Inflammation and Apoptosis in Weaning Rats and HEK-293 Cells - Shi, Yueyue; Tian, Chongmei; Yu, Xinfen; Fang, Yuejuan; Zhao, Xinyu; Zhang, Xiaoxi; Xia, Daozong (Frontiers in Pharmacology, 2020)
Lead (Pb) is an important environmental pollutant. Oxidative stress and the inflammatory response have been postulated as mechanisms involved in lead-induced renal damage. Smilax glabra Roxb. has been used for treatment of heavy-metal poisoning in China for 500 years. We investigated S. glabra flavonoids extract (SGF) could attenuate lead acetate-induced nephrotoxicity in weaning rats and human embryonic kidney (HEK)-293 cells, and investigated the possible mechanisms. Compared with Pb exposed group of weaning rats, SGF could significantly promote lead excretion in the blood and kidney, and increase the content of the renal-function indicators blood urea nitrogen, serum uric acid, and serum creatinine. SGF could improve the glomerular filtration rate (GFR) and histologic changes in the kidneys of weaning rats exposed to Pb. SGF could also reduce lead-induced cytotoxicity, improve DNA damage-induced apoptosis and cleaved caspase-3-mediated apoptosis in HEK-293 cells stimulated with Pb. SGF significantly increased the activity of the antioxidant enzymes superoxide dismutase, glutathione peroxidase and catalase, and decreased excessive release of reactive oxygen species (ROS) and malondialdehyde in the kidneys of the weaning rats and in HEK-293 cells. The antioxidant mechanism of SGF related to activation of the Kelch-like ECH-associated protein 1/nuclear-factor-E2-related factor 2/hemeoxygenase-1(Keap1/Nrf2/HO-1) pathway. SGF could inhibit secretion of interleukin (IL)-1β, IL-6 and tumor necrosis factor (TNF)-α induced by Pb in vivo and in vitro. The anti-inflammatory mechanism of SGF related to inhibition of ROS and pro-inflammatory cytokines triggered the nuclear factor-kappa B (NF-κB) pathway through blockade of inhibitors of I-κB degradation, phosphorylation of NF-κB p65, and nuclear translocation of p65. Our findings indicate that SGF could be a natural antioxidant and anti-inflammatory agent for treating lead-induced nephrotoxicity.